PENGGUNAAN CONTEXTUAL LEARNING AND TEACHING DALAM PELATIHAN BAHASA INGGRIS BAGI PASSENGER SERVICE OFFICER KERETA CEPAT JAKARTA BANDUNG - Puspitasari, Armyta; Fikria, Ainun; Isti Pratiwi, Damar; Leliana, Arinda; Fitria, Nurul (Education and Talent Development Center of Indonesia (ETDC Indonesia), 2023)
In the framework of planning the Jakarta-Bandung Fast Train (KCJB) which will be operated at the end of 2023, it is necessary to have services prepared to serve prospective passengers, namelyPassenger Service Officer on Train (PSOT). For this reason, the ability to use English for PSOT is important to support international passenger communication. The purpose of this activity is to provide English language training for Passanger Service Officers using the methodContextual Learning and Teaching (CTL). Evaluation of this activity using a Google form with a Likert scale. The results of the evaluation of this activity showed that the training activities benefited PSOT's work with the evaluation results of 75.12% stating that it was very good for the appearance and abilities of the presenters, and 73.55% choosing excellent criteria on the material criteria.